Pengelolaan Biaya Operasional Sekolah Di MI El - Nur El - Kasysyaf IV - Avissa, Muidzotun; Malasari, Hanifah Nur; Aziz, Muhammad Abdul; Faishal, Muhammad Farras; Permana, Hinggil (Widya Balina, 2024)
ABSTRACT The School Operational Assistance (BOS) program is under the responsibility of the Ministry of Education and Culture, and the Ministry of Religious Affairs plays an important role in its implementation, distribution, and management. The Ministry of Education and Culture, the Ministry of Religious Affairs, and the Technical Ministry responsible for the implementation and management of the BOS program must issue technical guidelines for the use of BOS funds, which should guide the use of funds. This study aims to explain how school operational assistance (BOS) funds are managed at MI El-Nur El-Kasysyaf IV. This research employs a qualitative approach, with data collection techniques such as interviews, documentation, and observation being very important methods for collecting data. ABSTRAK Program Bantuan Operasional Seklah (BOS) berada di bawah tanggung jawab Kementerian Pendidikan dan Kebudayaan, Kementerian Agama berperan penting dalam pelaksanaan, penyaluran dan pengelolaannya. Penggunaa dana harus berpedoman pada petunjuk teknis penggunaan dana BOS yang diterbitkan oleh Kementerian Pendidikan dan Budaya, Kementerian Agama, serta diawasi oleh Kementeri Teknis yang membidangi pelaksanaan dan pengelolaan program BOS. Penelitian ini berusaha untuk menjelaskan pengelolaan dana Bantuan Operasional Sekolah (BOS) di MI El-Nur El-Kasysyaf IV. Penelitian ini menggunakan pendekatan kualitatif, dengan teknik pengumpulan data berupa wawancara, dokumentasi, dan observasi merupakan metode yang sangat penting untuk mengumpulkan data.